Evaluation of automatic cell free DNA extraction metrics using different blood collection tubes - Daniel Andersson; Helena Kristiansson; Manuel Luna Santamaría; Huma Zafar; Ivan Mijakovic; Åsa Torinsson Naluai; Anders Ståhlberg (Scientific Reports)
Abstract Liquid biopsies and cell-free DNA (cfDNA) analysis are used in numerous clinical applications. The amount of cfDNA is generally limited and many approaches require assessment of individual molecules. Optimized pre-analytical steps are therefore fundamental for accurate interpretation. Here, we established an automated extraction approach providing cfDNA of high yield and quality. We analyzed 649 blood plasma samples collected from 23 healthy individuals and assessed the performance of four different blood collection tubes, time between sampling and plasma isolation and number of centrifugation steps. CfDNA was quantified by fluorometric analysis and quantitative polymerase chain reaction, while contaminating cellular DNA was assessed by quantitative polymerase chain reaction and parallel capillary electrophoresis. Data showed that cfDNA yield depends on both choice of blood collection tube and time between sampling and plasma isolation. Plasma isolated directly after sampling in K2EDTA tubes and plasma isolated within one week from preservative Streck tubes provided high cfDNA yield. We demonstrate that contaminating cellular DNA may be challenging to detect and that quantitative polymerase chain reaction and parallel capillary electrophoresis provide complementary information. In summary, reliable cfDNA analysis requires optimized experimental workflows, where the effects of pre-analytical factors should be considered in study designs and in clinical implementations.